2012
DOI: 10.1002/rrq.008
|View full text |Cite
|
Sign up to set email alerts
|

Reading Coaches and the Relationship Between Policy and Practice

Abstract: Many educational policy initiatives use instructional coaching to accomplish their goals. Yet we know little about the role of reading coaches in mediating the relationship between policy and teachers’ classroom practice. In this article, we investigate the role of reading coaches in mediating the relationship between Reading First policy and teachers’ classroom practice. We conducted an in‐depth, longitudinal case study of one urban elementary school in Massachusetts, starting the year before the onset of Rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
176
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(186 citation statements)
references
References 59 publications
3
176
0
7
Order By: Relevance
“…Framing is used to characterise a problem in a particular way, persuade others to one's opinion, or to counter others' claims. Scholars have previously used frame theory and similar approaches to investigate school board deliberations (Asen et al, 2011;Tracy & Dimock, 2004), local negotiations of policy implementation (Coburn, 2006;Coburn & Woulfin, 2012), andmost relevant to our work -data use in decision making (Coburn et al, 2009;Park et al, 2013).…”
Section: Analysing the Content And Flow Of Deliberation With Frame Thmentioning
confidence: 99%
“…Framing is used to characterise a problem in a particular way, persuade others to one's opinion, or to counter others' claims. Scholars have previously used frame theory and similar approaches to investigate school board deliberations (Asen et al, 2011;Tracy & Dimock, 2004), local negotiations of policy implementation (Coburn, 2006;Coburn & Woulfin, 2012), andmost relevant to our work -data use in decision making (Coburn et al, 2009;Park et al, 2013).…”
Section: Analysing the Content And Flow Of Deliberation With Frame Thmentioning
confidence: 99%
“…Some existing studies analyze the effects of coaching on student outcomes without considering the mediating factor of changing 15 instructional practices (e.g., Biancarosa et al, 2010;Elish-Piper & L'Allier, 2011;Lovett et al, 2008;Marsh et al, 2008), while others consider associations between coaching and instructional practices with no direct evidence that these changes to instruction have a positive effect on student achievement (e.g., Brown et al, 2007;Cantrell & Callaway, 2008;Coburn & Woulfin, 2012). The present study attempts to isolate, albeit in a nonexperimental way, the specific role of coaching in relation to instruction and student outcomes.…”
Section: The Present Studymentioning
confidence: 99%
“…Wendy's words, "I feel like I'm cheating by just sitting there talking with them," reflect what a fundamental restructuring of beliefs this was for her. As in Coburn and Woulfin's (2012) research, which found that teachers were more likely to respond with accommodation when a policy message came from a coach, Wendy's work with her STARI coach caused her to change her approach to reading instruction.…”
mentioning
confidence: 94%
“…Evidence from a recent national survey, in fact, indicates that school and district leaders are hungry for timely, relevant research to fuel their ongoing work (Penuel et al, 2016). Researchers who aim to meet this demand and ensure the relevance of their work will likely need to alter their practices in ways that bring them into tighter alignment with leaders and practitioners closer to the ground (Coburn & Stein, 2010).…”
mentioning
confidence: 99%